(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
In the digital age, online stalking has emerged as a pervasive threat, partic ularly affecting women in India. This study explores the social and psycho logical impacts of cyberstalking on women based on qualitative interviews, surveys, and existing literature. Women face a range of psychological con sequences, including anxiety, fear, depression, and a sense of helplessness. Socially, victims often face stigma, self-isolation, and an erosion of trust in digital communications. Cultural norms and gendered power dynamics further exacerbate this issue, limiting women’s ability to seek legal recourse or assistance. The normalization of digital surveillance and inadequate enforcement of cyber laws contribute to an environment where victims are often silenced. This research highlights the urgent need for widespread dig ital literacy, legal reform, and support systems to combat online stalking and create safer online environments for women. Addressing these chal lenges is essential to promote gender equality and mental health in India’s rapidly evolving digital society.